ALUR PENYELIDIKAN SURVEILANS DAN DIAGNOSA DINI COVID-19 DI KOTA BAUBAU - La Ode Yusman Muriman; Taswin Taswin; LM Khairul Razy (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Currently the data on the spread of Covid-19 continues to increase, the World Health Organization (WHO) has reported the number of Covid-19 cases reaching 20,126.45 cases with 737,285 deaths worldwide and there are several health workers who have been reported to have been infected. Indonesia has confirmed cases of Covid-19 on November 25, 2021. Cumulatively, 4,254,443 people have been confirmed positive for COVID-19. Baubau City reported the number of Covid-19 cases on March 23, 2021, which was 10,221 cases. This study aims to determine the Flow of Surveillance Investigations and Early Diagnosis of Covid-19 in Baubau City. The type of research used is quantitative with a descriptive observational research design. The population and sample in this study were surveillance officers, assistant surveillance officers working at the Puskesmas and surveillance officers at the Baubau City Health Office totaling 35 people. The analysis used is univariate analysis. The results of this study indicate that from 35 Puskesmas surveillance officers conducting epidemiological investigations in communities with symptoms, as many as 34 people (100%) and several Puskesmas surveillance officers conducting epidemiological investigations in communities without symptoms, as many as 26 people (76.5%). , Puskesmas surveillance officers who categorize based on people during epidemiological investigations are 32 people (94.1%), Puskesmas surveillance officers who carry out categorization based on places during epidemiological investigations are 26 (76.5%), how to know someone has been exposed to covid -19 health center surveillance officers by looking at the symptoms felt by the patient, by looking at the travel history of the patient from outside/in the area, by looking at the history of direct contact of the patient with someone, by looking at the results of the rapid examination and swab test of the patient, as many as 28 (82.4 %) and all surveillance officers did The treatment is in accordance with the patient's condition, namely 34 people (100%) both those who meet and do not fulfill the DO of patients under supervision in the community who travel (people under supervision) and (patients under supervision). Surveillance activities in terms of data collection at each Baubau City Health Center, namely the type of data collected in the form of data on morbidity, mortality and community demographic data and sources of Covid-19 data obtained are categorized by person, place and time. There are several surveillance officers who do not categorize by person and place only by time, and surveillance data is collected on people who have symptoms and do not have symptoms. It is hoped that surveillance officers at the Baubau City Health Office will maximize ongoing surveillance activities to reduce the incidence of COVID-19 disease in the community.